2019
DOI: 10.1038/s42003-019-0477-4
|View full text |Cite
|
Sign up to set email alerts
|

Plastoquinone homoeostasis by Arabidopsis proton gradient regulation 6 is essential for photosynthetic efficiency

Abstract: Photosynthesis produces organic carbon via a light-driven electron flow from H 2 O to CO 2 that passes through a pool of plastoquinone molecules. These molecules are either present in the photosynthetic thylakoid membranes, participating in photochemistry (photoactive pool), or stored (non-photoactive pool) in thylakoid-attached lipid droplets, the plastoglobules. The photoactive pool acts also as a signal of photosynthetic activity allowing the adaptation to chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 50 publications
4
35
0
Order By: Relevance
“…We found that the abc1k3 mutant has no photosynthetic defect compared to the wild type under the tested conditions. However, by stacking this mutation with abc1k1 we observe a partial alleviation of all the photosynthetic defects previously reported in abc1k1 (Shikanai et al, 1999;Martinis et al, 2014;Pralon et al, 2019). Surprisingly, the phenotype complementation does not originate from an effect on the size of the photoactive PQ pool but rather from an effect on PQ mobility in the thylakoid membrane.…”
Section: Introductionsupporting
confidence: 45%
See 4 more Smart Citations
“…We found that the abc1k3 mutant has no photosynthetic defect compared to the wild type under the tested conditions. However, by stacking this mutation with abc1k1 we observe a partial alleviation of all the photosynthetic defects previously reported in abc1k1 (Shikanai et al, 1999;Martinis et al, 2014;Pralon et al, 2019). Surprisingly, the phenotype complementation does not originate from an effect on the size of the photoactive PQ pool but rather from an effect on PQ mobility in the thylakoid membrane.…”
Section: Introductionsupporting
confidence: 45%
“…The kinetic of the subsequent reoxidation induced by FAR were followed with a saturating flash of actinic light (1000 µmol m −2 s −1 for 100 µs) to fully reduce the ETC or without so that the ETC was fully oxidized. The ratio between the lag times between the FAR onset and the beginning of the P 700 oxidation in these two conditions is used as a proxy for the number of available electrons per PSI (Pralon et al, 2019).…”
Section: P 700 Oxidationmentioning
confidence: 99%
See 3 more Smart Citations